Colorectal cancer stem cells crosstalk in tumor immune microenvironment and targeted therapeutic strategies - Duan, Yuxuan; Li, Anshu; Miao, Daojia; Tan, Diaoyi; Wang, Keshan; Shi, Jian (Frontiers in Immunology, 2025)
Colorectal cancer (CRC) remains a formidable clinical challenge due to therapy resistance, metastasis, and relapse. Central to these processes are colorectal cancer stem cells (CCSCs), a dynamic subpopulation endowed with self-renewal capacity, plasticity, and heterogeneity. This review synthesizes recent advancements in understanding how CCSCs orchestrate tumor progression through intricate bidirectional crosstalk with the tumor immune microenvironment (TIME). We begin by elucidating the cellular origins of CCSCs, their profound intratumoral heterogeneity, and their remarkable phenotypic plasticity—driven by genetic, epigenetic, and metabolic reprogramming—which collectively serve as the root cause of therapeutic failure. A significant portion of our discussion is dedicated to deconstructing the immunosuppressive niche co-opted by CCSCs. We detail mechanisms of immune evasion and tolerance, highlighting how CCSCs modulate innate and adaptive immune cells—including NK cells, Tregs, dendritic cells, macrophages, neutrophils, and myeloid-derived suppressor cells—to foster an environment that supports stemness and suppresses cytotoxic attack. This reciprocal interaction forms a vicious cycle that perpetuates tumor survival and progression. Finally, we critically evaluate emerging therapeutic strategies that concurrently target CCSC-specific vulnerabilities and counteract immunosuppression. We explore the limitations of conventional chemotherapy and the promise of targeted therapies (e.g., Wnt inhibitors), immunotherapies (e.g., CAR-T, bispecific antibodies), and combination regimens designed to remodel the TIME and eradicate the CCSC reservoir. By integrating insights from single-cell omics and spatial biology, this review provides a comprehensive framework for overcoming therapy resistance and proposes novel precision medicine approaches for CRC.